Construction of Y‐Doped BiVO4 Photocatalysts for Efficient Two‐Electron O2 Reduction to H2O2. Issue 25 (22nd March 2023) - Dai, Dujuan; Bao, Xiaolei; Zhang, Qianqian; Wang, Zeyan; Zheng, Zhaoke; Liu, Yuanyuan; Cheng, Hefeng; Dai, Ying; Huang, Baibiao; Wang, Peng
Abstract: Photocatalytic hydrogen peroxide (H2 O2 ) production on BiVO4 photocatalysts using water and oxygen as raw materials is a green and sustainable process. However, the photocatalytic efficiency of pristine BiVO4 is limited by severe charge recombination. In this work, rare earth element Yttrium (Y) doped BiVO4 photocatalysts were fabricated by the hydrothermal method. In the photocatalytic H2 O2 production experiment, the optimized Y‐doped BiVO4 photocatalyst produced 114 μmol g −1 h −1 of H2 O2 under simulated sunlight (AM1.5) irradiation, which is four times higher than production activity of pure BiVO4 (26 μmol g −1 h −1 ). Density functional theory (DFT) calculation revealed that Y doping can enhance oxygen adsorption on the BiVO4 photocatalyst surface. Mechanistic investigations suggest that the doping process induces the in situ formation of monoclinic/tetragonal BiVO4 heterojunction, which further promotes the photogenerated carriers separation efficiency. Abstract : Y doping induces the formation of monoclinic/tetragonal BiVO4 heterojunction and improves the O2 adsorption, which facilitates the two‐electron reduction of O2 . Compared with original BiVO4, the photocatalytic H2 O2 production activity of Y‐doped BiVO4 is significantly increased.